Influence of the drying method on the physicochemical properties, volatile compounds, and odor characteristics of edible insect oils - Ji Yoon Cha; Mi-Ran Kim; Yea-Ji Kim; Jeong Heon Kim; Jaejoon Han; Yun-Sang Choi (Food Research International, 2025)

Impact of thawing methods and packaging sizes on the physicochemical and microbial quality of frozen kimchi - Hee Eun Kim; Yun-Jeong Choi; Dong Hyun Park; Min Jung Lee; Minji Kim; Sung Jin Park; Ji Young Choi; Mi Ran Kang; Sung Hee Park; Mi-Ai Lee (International Journal of Refrigeration, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Deciphering the links: Fragmented polystyrene as a driver of skin inflammation - Gyeong Bae Song; Jisoo Nam; Sangmin Ji; Gijeong Woo; Soojeong Park; Bokyung Kim; Jeein Hong; Myung Gil Choi; Seokheon Kim; Chaerin Lee; Wonchul Lim; Sangwoon Yoon; et al. (Journal of Hazardous Materials, 2024)

Variation of volatile compounds and sensory profile for Protaetia brevitarsis larvae fermented with lactic acid bacteria and yeast - Ji Yoon Cha; Jaejoon Han; JeongAe Heo; Hwan Hee Yu; Yea-Ji Kim; Hae Won Jang; Mi-Ran Kim; Yun-Sang Choi (Food Chemistry, 2024)

Overexpression of S-adenosylmethionine synthetase gene enhances polyamine content and antioxidant activity in transgenic plants - Hye Lim Choi; Ji Won Seo; Mi Ran Jeon; Jae Geun Lee; Ji Hye Yoo; Chang Yeon Yu; Eun Soo Seong (Brazilian Journal of Botany, 2023)

Relationship between PM1.0 and PM2.5 in urban and background areas of Republic of Korea - Sujin Kwon; Soo Ran Won; Hyung Bae Lim; Sung Chul Hong; Yong Mi Lee; Ji Yun Jung; Sung-Deuk Choi; Sang-Jin Lee; Seungmee Oh; Ju Young Kim; Yong Pyo Kim; Hye Jung Shin; et al. (Atmospheric Pollution Research, 2023)

Multiple low-dose radiation-induced neuronal cysteine transporter expression and oxidative stress are rescued by N-acetylcysteine in neuronal SH-SY5Y cells - Ji-Young Yoo; Ye-Ji Lee; Yu-Jin Kim; Tai-Kyoung Baik; Jun-Ho Lee; Mi‑Jo Lee; Ran-Sook Woo (NeuroToxicology, 2023)

Analysis of genetic diversity in the bioenergy crop Miscanthus via ISSR and RAPD markers - Eun Soo Seong; Mi Ran Jeon; Ji Won Seo; Jae Geun Lee; Chang Yeon Yu (Journal of Crop Science and Biotechnology, 2022)

Characterization of PyGUS gene silencing in the red macroalga, Pyropia yezoensis - Yoon Ju Shin; Jong-Min Lim; Ji Hyun Park; Dong-Woog Choi; Mi Sook Hwang; Eun-Jeong Park; Sung Ran Min; Suk Weon Kim; Won-Joong Jeong (Plant Biotechnology Reports, 2016)

Study of Photo and Thermoluminescence Properties to Identify Irradiated Dried-Fishery Products - Moon-Young Kim; Jae-Jun Ahn; Kashif Akram; Gui-Ran Kim; Mi-Seon Jeong; Ji-Young Kwak; Joong-Ho Kwon (Journal of Aquatic Food Product Technology, 2016)

Transcriptomic study of mouse embryonic neural stem cell differentiation under ethanol treatment - Chanchal Mandal; Ji Hyun Park; Mi Ran Choi; Sun Hwa Kim; Abimbola Comfort Badejo; Jin Choul Chai; Young Seek Lee; Kyoung Hwa Jung; Young Gyu Chai (Molecular Biology Reports, 2015)

Characterization and miRNA-mediated posttranscriptional regulation of vitelline membrane outer layer protein I in the adult chicken oviduct - Sang In Lee; Mi-Ran Ji; Ye-Jin Jang; Mi-hyang Jeon; Jeom Sun Kim; Jin-Ki Park; Ik-Soo Jeon; Sung June Byun (In Vitro Cellular & Developmental Biology - Animal, 2015)

Functional Analysis of Histone Demethylase Jmjd2b on Lipopolysaccharide-Treated Murine Neural Stem Cells (NSCs) - Nando Dulal Das; Mi Ran Choi; Kyoung Hwa Jung; Ji Hyun Park; Hyung Tae Lee; Amitabh Das; Seung Hyun Kim; Young Gyu Chai (Neurotoxicity Research, 2013)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Ethanol-induced small heat shock protein genes in the differentiation of mouse embryonic neural stem cells - Mi Ran Choi; Kyoung Hwa Jung; Ji Hyun Park; Nando Dulal Das; Mi Kyung Chung; Ihn Geun Choi; Boung Chul Lee; Kyoung Sun Park; Young Gyu Chai (Archives of Toxicology, 2011)

An atypical soybean leucine-rich repeat receptor-like kinase, GmLRK1, may be involved in the regulation of cell elongation - Sunghan Kim; Su-Jin Kim; Yun-Jeong Shin; Ji-Hye Kang; Mi-Ran Kim; Kyoung Hee Nam; Myeong-Sok Lee; Suk-Ha Lee; Yul-Ho Kim; Soon-Kwan Hong; Desh Pal S. Verma; Jong-Yoon Chun; et al. (Planta, 2009)